2016
DOI: 10.1007/s40279-016-0669-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise on Ovulation: A Systematic Review

Abstract: Several clear gaps have been identified in the existing literature. Short-term studies of over-training have not always produced the disturbance to ovulation identified in the observational studies, bringing up the question of the roles of longer term training and chronic energy deficit. We believe this merits further investigation in specific cohorts, such as professional athletes. Another gap is the complete absence of exercise-based interventions in anovulatory women with a normal body mass index (BMI). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
77
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 72 publications
1
77
0
2
Order By: Relevance
“…The IMPROV-IT trial will determine the effect of HIT on reproductive, cardiovascular, metabolic and psychological health in women with PCOS. The trial will contribute evidence of more specific exercise protocols in the treatment and management of PCOS for clinicians and answer some of the current limitations addressed by both the International evidence-based guidelines for the assessment and management of PCOS4 and several systematic reviews 2 12 25 58. This trial is highly relevant and important as PCOS is a major burden for the women with PCOS, the health services and society.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The IMPROV-IT trial will determine the effect of HIT on reproductive, cardiovascular, metabolic and psychological health in women with PCOS. The trial will contribute evidence of more specific exercise protocols in the treatment and management of PCOS for clinicians and answer some of the current limitations addressed by both the International evidence-based guidelines for the assessment and management of PCOS4 and several systematic reviews 2 12 25 58. This trial is highly relevant and important as PCOS is a major burden for the women with PCOS, the health services and society.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies have demonstrated positive effects in reproductive outcomes after exercise, with concomitant improvements in insulin sensitivity and/or visceral fat 20–24. However, more knowledge is needed about the underlying mechanisms for improvement in fertility after exercise training, as discussed in several systematic reviews on lifestyle interventions and fertility 12 25 53 54. HIT has shown to be time efficient, safe and well tolerated, with positive effects on metabolic and cardiovascular risk factors in several studies 29 55 56.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is, however, a lack of good-quality randomised controlled trials comparing types of physical activity, intensity and durations on reproductive outcomes and the focus have been mainly on weight loss. 15 …”
Section: Discussionmentioning
confidence: 99%